Фінансова звітність як інструмент прийняття управлінських рішень у приватному та державному секторах економіки - Лоскоріх Габріелла; Gabriella Loskorikh; Loszkorih Gabriella; Перчі Оксана; Oksana Perchi; Pércsi Oxána; Стойка Наталія; Natalia Stoika; Sztojka Natália (Видавничий дім «Гельветика», 2025)
Резюме. У сучасних економічних умовах, що характеризуються нестабільністю, цифровізацією та посиленням вимог до прозорості, фінансова звітність набуває особливого значення як у приватному, так і в державному секторах. Проте підходи до її складання та використання в цих секторах суттєво різняться через специфіку цілей, джерел фінансування, користувачів інформації та нормативної бази. Метою статті є дослідження ролі фінансової звітності як інструменту прийняття управлінських рішень у приватному та державному секторах економіки, визначення подібностей і відмінностей у її використанні, а також формулювання пропозицій щодо підвищення ефективності аналітичного використання звітних даних. У статті здійснено порівняльну характеристику національних положень (стандартів) бухгалтерського обліку в приватному та державному секторах, проаналізовано основні аспекти та охарактеризовано форми фінансової звітності в обох секторах. Наведено пропозиції щодо удосконалення методів аналітичного використання звітних даних для підвищення ефективності прийняття рішень у обох секторах економіки.

Abstract. In the current economic conditions, characterized by instability, digitalization, and increasing demands for transparency, financial reporting becomes particularly significant in both the private and public sectors. However, the approaches to its preparation and use in these sectors differ significantly due to the specific objectives, sources of funding, information users, and regulatory frameworks. The purpose of this article is to explore the role of financial reporting as a tool for management decision-making in both the private and public sectors of the economy, identify the similarities and differences in its use, and formulate suggestions to improve the effectiveness of the analytical use of reporting data. In the private sector, financial reporting not only serves an accounting function but also acts as a key tool for strategic and tactical management. It ensures transparency, comparability, and reliability of information, which is essential for external users such as investors, banks, partners, and regulatory authorities, as well as for internal analysis. In the public sector, financial reporting is primarily used to ensure compliance with budgetary legislation, the accuracy of accounting in accordance with the adopted accounting policy, and the alignment of reported data with the requirements of current standards. Financial reporting in the public sector, when supported by appropriate analytical tools, can serve as a powerful basis for management decision-making. It allows for the evaluation of the financial stability of a public institution, the level of resource utilization, and the alignment between planned and actual performance. This article provides a comparative analysis of national accounting standards in private and public sectors, examines key aspects, and characterizes the forms of financial reporting in both sectors. The functions of financial reporting are detailed, and suggestions for improving the methods of analytical use of reporting data to enhance decision-making effectiveness in both sectors of the economy are provided. By improving the analytical capacity of financial reports, both private enterprises and public institutions can foster better-informed, more effective management decisions, contributing to greater economic stability and development.
Financial reporting as a tool for management decision-making in the private and public sectors of the economy
Весь випуск: https://www.economdevelopment.in.ua/index.php/journal/issue/view/36
Keywords: фінансова звітність; облік; національні положення (стандарти) бухгалтерського обліку; національні положення (стандарти) бухгалтерського обліку в державному секторі; приватний сектор; financial reporting; accounting; national accounting standards; national accounting standards in the public sector; private sector